2019
DOI: 10.3390/v11060542
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Antibodies against Sindbis Virus in the Israeli Population: A Nationwide Cross-Sectional Study

Abstract: Sindbis virus (SINV) is a mosquito-borne alphavirus circulating globally. SINV outbreaks have been mainly reported in North-European countries. In Israel, SINV was detected in 6.3% of mosquito pools; however, SINV infection in humans has rarely been diagnosed. A serologic survey to detect SINV IgG antibodies was conducted to evaluate the seroprevalence of SINV in the Israeli population. In total, 3145 serum samples collected in 2011–2014, representing all age and population groups in Israel, were assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A considerable number of projects have used the INSB, thus yielding a large number of papers published throughout the years [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Some of these have evaluated immunity of the population against vaccine-preventable diseases (diphtheria [ 21 ], Bordetella pertussis [ 22 ], influenza [ 23 ], hepatitis A [ 24 ], hepatitis B [ 25 ], measles [ 26 ], mumps [ 27 ], rubella [ 27 , 28 ], varicella [ 29 ], and polio [ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A considerable number of projects have used the INSB, thus yielding a large number of papers published throughout the years [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Some of these have evaluated immunity of the population against vaccine-preventable diseases (diphtheria [ 21 ], Bordetella pertussis [ 22 ], influenza [ 23 ], hepatitis A [ 24 ], hepatitis B [ 25 ], measles [ 26 ], mumps [ 27 ], rubella [ 27 , 28 ], varicella [ 29 ], and polio [ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these have evaluated immunity of the population against vaccine-preventable diseases (diphtheria [ 21 ], Bordetella pertussis [ 22 ], influenza [ 23 ], hepatitis A [ 24 ], hepatitis B [ 25 ], measles [ 26 ], mumps [ 27 ], rubella [ 27 , 28 ], varicella [ 29 ], and polio [ 30 ]). Other projects have assessed exposure of the population to infectious agents, including emerging ones (herpes simplex viruses 1 and 2 [ 31 ], Helicobacter pylori [ 32 ], Toxoplasma gondii [ 33 ], hepatitis E [ 34 ], parvovirus [ 35 ], West Nile Fever Virus [ 36 ], MERS-CoV, Sindbis [ 37 ], and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)). Further activities of the INSB are published on the Israel Center for Disease Control website ( accessed on 25 February 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In Israel, the virus seems to be constantly circulating in the country recently, as SINV-I was detected in mosquito pools collected during the period of 2004-2006 and 2013-2015 [304]. Also, a serological survey conducted from 2011 to 2014 demonstrated a prevalence of IgG anti-SINV of 1.9−3.6% [305]. In Germany, Jöst et al showed [306] the presence of SINV in mosquitoes collected in the southwest region of the country in 2009.…”
Section: Potential For Future Outbreaksmentioning
confidence: 99%